Current Topics (The Muslim world, 1937)
Unveiling in Iran What Islam Wants of the West Moslem Schoolboys The Moslem Feast, Nebi Musa Arab Women with a Profession In Memory of the Prophet Mohammed The Henry Martyn School of Islamics, Lahore A Mosque for London Le Père Henri Lammens The Millennial Celebration of Al-Azhar